(Re)conceptualizing movement behavior in sport as a problem-solving activity - Myszka, Shawn; Yearby, Tyler; Davids, Keith (Frontiers in Sports and Active Living, 2023)
The use of the term problem-solving in relation to movement behavior is an often-broached topic within kinesiology. Here we present a clear rationale for the concept of problem-solving, specifically pertaining to the skilled organization of movement behaviors in sport performance, and the respective processes that underpin it, conceptualized within an ecological dynamics framework. The movement behavior that emerges in sport can be viewed as a problem-solving activity for the athlete, where integrated movement solutions are underpinned by intertwined processes of perception, cognition, and action. This movement problem-solving process becomes functionally aligned with sport performance challenges through a tight coupling to relevant information sources in the environment, which specify affordances offered to the athlete. This ecological perspective can shape our lens on how movements are coordinated and controlled in the context of sport, influencing practical approaches utilized towards facilitating dexterity of athletes. These ideas imply how coaches could set alive movement problems for athletes to solve within practice environments, where they would be required to continuously (re)organize movement system degrees of freedom in relation to dynamic and emergent opportunities, across diverse, complex problems. Through these experiences, athletes could become attuned, intentional, and adaptable, capable of (re)organizing a behavioral fit to performance problems in context—essentially allowing them to become one with the movement problem.